The Ottoman slave trade and its suppression, 1840-1890 - Toledano, Ehud R. (Princeton studies on the Near East., 1982)
This book is a historical account of the slave trading system of the Ottoman Empire in the second half of the nineteenth century and of the attempts, which were eventually successful, to suppress it. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Le.